Anarchisme et Catalanisme en exil en France, 1939-1977 - Phryné Pigenet (Cahiers de Civilisation Espagnole Contemporaine)
In the absence of true doctrinal reflection on the national fact, in spite of their anti-state and internationalism, the libertarians of Catalonia shared a certain cultural proximity with the Catalanists. Despite Franco's repression, the legacy of the Spanish War led to an anti-Catalanist doctrinal twisting in Catalan libertarians between anarchist orthodoxy and nostalgia for the mother country, as evidenced by the publication of exile in Catalan language, « Terra Lliure ». Nevertheless his feeble audience was but an imperfect reflection of the practices of the exiled militants of France.